The role of filamentous phage in the development of Pseudomonas aeruginosa biofilms - Manisha Mukherjee (2015)
Bacteriophage have been known for more than 100 years and the majority of phage described cause cell lysis and death. In contrast, filamentous phage have been shown to maintain a stable relationship without harming its bacterial host. It has recently been shown that filamentous phage have a range of effects on the host, including contributing to the virulence of Vibrio cholerae. Pf4, a filamentous phage of Pseudomonas aeruginosa PAO1, has been shown to contribute significantly to the biofilm life-cycle, including the formation of small colony variants, biofilm cell death, biofilm stability and virulence in a mouse model. These effects were primarily linked to the appearance of a superinfective form of the Pf4, which was observed at the time of dispersal. Pf4 related sequences appear in most strains of P. aeruginosa suggesting that this phage may confer a selective advantage on the host. Hence, understanding the phage - host (Pf4 – PAO1) interaction is essential to delineate the role of filamentous phage in the development of PAO1 biofilms. The wild type PAO1 and Pf4 deletion mutant were fluorescently labelled and co-inoculated into flow cells to determine if the prophage represented a selective advantage for PAO1. Quantitative image analysis indicated that the two strains stably co-existed up to day 3. The Pf4 mutant comprised 49.43 % and 42.62 % of the biofilm biomass on days 1 and 3 respectively. After day 3 the biofilm biomass of the Pf4 mutant decreased, to 37.73 % on day 5 and from day 7 onward, the Pf4 mutant represented less than 30 % of the total biofilm suggesting that the wild-type was capable of outcompeting the phage mutant. Phages were added back to PAO1 and Pf4 mutant biofilms and the effect of the phage on the biofilm viability was assessed. Confocal microscopy analysis of the treated biofilms after 24 h of exposure to Pf4 wild-type phage, indicated a significant increase in the proportion of non-viable cells in Pf4 mutant biofilms, while no significant difference was observed in PAO1 biofilm. In contrast, an increase in non-viable cells was observed when the biofilms of both PAO1 and Pf4 mutant were challenged with superinfective Pf4 phage. These results suggest that superinfection may play an important role in biofilm development. Proteomic analysis of planktonic cells showed induction of proteins associated with pyoverdine production in the absence of the Pf4 phage. Additionally, the exogenous add-back of phage to the Pf4 knock-out strain resulted in reduction of pyoverdine related proteins, which further supports the involvement of Pf4 phage in suppression of these proteins when present as a prophage in the PAO1 wild-type. The proteomic results were further validated by qRT-PCR. These suggest that Pf4 phage may play an important role in regulating pyoverdine synthesis which is an important virulence factor for P. aeruginosa PAO1. This work also focuses on the development of a mixed species biofilm model comprised of Pseudomonas protegens, Pseudomonas aeruginosa and Klebsiella pneumoniae to understand the interspecies interaction and to facilitate studies on how bacteriophage impact biofilm development and stability. The multispecies biofilm exhibited altered biofilm development compared to the single-species biofilms which suggests community level interactions in a structured consortium. Infection of the mixed species biofilm with the superinfective Pf4 phage did not affect cell death and dispersal, which was observed in superinfective phage infected P. aeruginosa single species biofilm. This suggests that the phage may not be able to infect the PAO1 cells in the mixed species community. Such, community level resistance offered to P. aeruginosa from phage infection might be due to the protection offered by other community members which are not targeted by the host specific phage.